Satisfaction of GP employees in GPHouse regarding transport services provided by Grameenphone - Plabon, Minhaz Ali Khan (BRAC University, 2013)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.